Expressions of Epistemic Possibility in Academic Writing in English as a Foreign Language - Bartholomeus Budiyono (Magister Scientiae, 2020)
Epistemic possibility operates with may and interchangeably with might that introduce a direct-unobservable effect in a modalized causal relation that reveals a semantic cause-and-effect compatibility. It also operates with could to introduce a direct-unobservable cause without any authoritative evidential, may to introduce a cause derived from an authoritative (indirect-unobservable) assumption through an informal fallacy. The presence of the possibility level is reinforced by other operators. The operator possible is used to introduce a direct-unobservable cause without any help of an authoritative evidential, a direct-unobservable cause derived from an authoritative assumption through an informal fallacy, a causal relation between direct-observable evidentials as commentary on an authoritative theory after factive causality. The operator seem also introduces direct-unobservable cause, but also falsifies a prima facie perception. In addition to the epistemic uses, the same operators also indicate factivity, i.e., factive may, factive might, factive possibility, neutral-factive could. Finally, there are cases of a simultaneous use of possibility operators. Throughout the analysis of the data, epistemic possibility is characterized with non-factivity and optionality, i.e., proposing a non-factive option or an array of options. It may also be identified as presenting criticism of an assumption, criticism of the data, criticism of the ongoing learning situation, threat, and appreciation of the data. Criticism may be very salient when it is followed by a relevant suggestion.